(untitled) - Yowelna Tarumasely; I Nyoman Sudana Degeng; Punaji Setyosari; A.J.E. Toenlioe (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to analyze the effect of self-regulated learning strategy and self-efficacy on the learning outcomes of understanding concepts for second semester Christian Religious Education students. The research subjects were 96 people who were divided into two groups namely the experimental and control groups. Data were obtained using Neil's self-efficacy questionnaire and tests to measure learning outcomes from conceptual understanding. The data analysis uses a two-way ANOVA. The results show that there are differences in learning outcomes in understanding concepts between self-regulated learning strategy and teacher regulated learning strategy, with high and low self-efficacy levels, and there is an interaction between learning strategies and self-efficacy on learning outcomes in conceptual understanding. This means that self-regulated learning strategy and self-efficacy have a better influence on the results of the conceptual understanding of Learning Theory. This study is beneficial for education systems, teachers, and students, as it reveals an effective way of learning and understanding concepts. It may also be beneficial for future researchers in the respective field.